Developing synthetic sandstones using geopolymer binder for constraining coupled processes in porous rocks - Markus Peltz; Laurence Warr; Sina Hale; Philipp Blum (SN Applied Sciences, 2023)
Article highlights A novel approach for developing synthetic sandstones at low temperatures using geopolymer binder is presented. A variety of material properties can be easily controlled which allows adaption to attain specific experimental requirements. Geopolymer-bound synthetic sandstones are an ideal material for studying thermally sensitive materials such as carbonates in reactive flow-through experiments.